The Portuguese revolution : state and class in the transition to democracy - Chilcote, Ronald H. (Rowman & Littlefield Publishers, 2010)
Building on decades of research, leading scholar Ronald H. Chilcote provides a definitive analysis of the 1974-1975 Portuguese revolution, which captured global attention and continues to resonate today. His study revisits a key historical moment to explain the revolution and its aftermath through periods of authoritarianism and resistance as well as representative and popular democracy. Exploring the intertwined themes of class, state, and hegemony, Chilcote builds a powerful framework for understanding the Portuguese case as well as contemporary political economy worldwide.
Keywords: Social change : Portugal : History : 20th century; State, The : History : 20th century; Democracy : Portugal : History : 20th century; Social classes : Portugal : History : 20th century; Social movements : Portugal : History : 20th century; Portugal : Politics and government : 1974-; Portugal : Social conditions : 20th century